If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + 4 + 3 = 17 Reorder the terms: 4 + 3 + X = 17 Combine like terms: 4 + 3 = 7 7 + X = 17 Solving 7 + X = 17 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + X = 17 + -7 Combine like terms: 7 + -7 = 0 0 + X = 17 + -7 X = 17 + -7 Combine like terms: 17 + -7 = 10 X = 10 Simplifying X = 10
| 25x-10-16X=3(3X-4)+2 | | 3y-5+y+33=8y+30-6y | | Y=0.493x-973.4 | | 58=11x+3 | | 13x+72=-7x-28 | | 11-3x+5=10 | | 6.4x+2.3x=-65.6 | | 5(x+5)+3=18 | | 17x+4=-21-8x | | 4(2x+1)-3x=14 | | 12x^4y^3-20x^2y=0 | | a^3-125= | | 8w+3=5w+7+4w | | 6.4x-2.3x=65.6 | | 8-3(5-x)=14 | | 6x+11x=85 | | 4x-9x+5=10 | | 2x^2y+4xy-24y= | | 6y+42=4y | | 7(3x+4)=5(5x-4) | | 12x+4y=20(x) | | 7g+h=-2 | | -6x+5=77 | | 4(3y+6m)+-6y+14m= | | 6+2x=4(x+3) | | 4n+2=-4n+-2 | | 3x^2-28x-20=0 | | 2t+x=19 | | s=t+4 | | 36c^2-84cd+49d^2= | | (2x-10)(x+2)=0 | | 12x+12=72 |